NUTRIENTS DIGESTIBILITY OF BALI CATTLE FEED GIVEN BASAL DIET WITH BIOSUPPLEMENTS BALI CATTLE COLON AND ORGANIC WASTE BACTERIA CONSORTIUM - I M., Mudita; Kayana, I G. N.; Wirawan, I W. (Jurnal Peternakan Tropika, 2017)
A research has been carried out to increasing feed nutrients digestibility of bali cattle given basal feed with biosupplements bali cattle colon and organic waste bacteria consortium. Three superior inocullants used in this study for production biosupplement SBS 12 K 12 , SBS 1 K 12 , SBS 12 K 1 . This research used a latin square designed four treatments and four observation periods. The treatments were fed basal diet without biosupplement (PS 0 ), fed basal diet with the first superior biosupplement “SBS 12 K 12 ” (PSB 1 ), fed basal diet with second superior biosupplement “SBS 1 K 12 ” (PSB 2 ), fed basal diet with third superior biosupplement “SBS 12 K 1 ” (PSB 3 ). The result research showed that given biosupplement bacteria consortium of bali cattle colon and organic waste (PSB1, PSB2, PSB3) increasing dry matter digestibility (66,19 – 66,64% vs 61,56%), organic matter digestibility (69,24 – 70,13% Vs 65,06%), crude protein digestibility (69,78 – 71,03% Vs 67,95%) and crude fiber digestibility (59,24 – 59,86% Vs 55,05%) of bali cattle fed basal diet based on agriculture waste. It was concluded that fermentation with bacteria consortium from bali cattle colon and organic waste were increased quality of ration based on rumen contents. Key words :   fermentation; bacteria consortium; bali cattle colon; organic waste ; Ration based on rumen contens